THREE NEW SPECIES OF BARBACENIA (VELLOZIACEAE) FROM TOCANTINS, BRAZIL - Alves, R. J. V.; Guimarães, A. R.; Sadala, R.; Lira, M.; da Silva, N. G. (Edinburgh Journal of Botany, 2018)
Three new species of the Neotropical genus Barbacenia (Velloziaceae, Pandanales) from Tocantins, Brazil, are described and illustrated, based on morphology and leaf anatomy. The known species richness of the genus is mapped within the countries of South America and the states of Brazil.